1976
DOI: 10.1007/bf01220641
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monosodium glutamate administration in the neonatal period on the diabetic syndrome in KK mice

Abstract: Summary. Administration of monosodium glutamate (MSG) to KK mice during the neonatal period resulted in a syndrome of obesity, stunting and hypogonadism. In some animals the genetic predisposition to diabetes was unmasked with the development of marked hyperglycaemia and or hyperinsulinaemia. Food intake was not increased compared to controls. The elevated plasma glucose and insulin in fed MSG treated mice fell rapidly with food deprivation. Glucose disposal was comparable in MSG treated and control mice after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Other obesity animal models are somewhat dependent on food intake, such as VMH lesion [28], or on their genetic origin, such as ob/ob mice and Zucker rats [29,30]. Results also show that MSGobese mice are hyperglycemic and present high insulin blood levels, as has been reported by other authors [31,32]. It has been reported that MSG-mice are tissue insulin resistant [33,34].…”
Section: Discussionsupporting
confidence: 60%
“…Other obesity animal models are somewhat dependent on food intake, such as VMH lesion [28], or on their genetic origin, such as ob/ob mice and Zucker rats [29,30]. Results also show that MSGobese mice are hyperglycemic and present high insulin blood levels, as has been reported by other authors [31,32]. It has been reported that MSG-mice are tissue insulin resistant [33,34].…”
Section: Discussionsupporting
confidence: 60%
“…Female offspring received a subcutaneous (sc) daily injection of monosodium glutamate (MSG; Sigma, St. Louis, MO, USA) diluted in buffer solution at a dosage of 2.2 mg/g body weight from the first to the tenth day of life [46]. Physiological saline was injected into control mice in equivalent volume.…”
Section: Methodsmentioning
confidence: 99%
“…The obesity was not caused by polyphagia. It was said by Iwase et al [3] and Cameron et al [1] that obesity without polyphagia is due to the amount and frequency of MSG injection.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the ventromedial nucleus of the hypothalamus was destroyed by injecting mice with goldthioglucose (GTG) [6,7] and that the injected mice showed polyphagia and obesity [8], thereafter becoming diabetic. On the other hand, there are few reports of injecting MSG into mice that already have a diabetic condition [1,9], and also few reports concerning diabetes in other experimental animals [3,5]. There is no report of ICR normal mice developing obesity without polyphagia and a diabetic condition by injecting MSG, and of the condition continuing over a long period.…”
Section: Introductionmentioning
confidence: 99%